Analisis Kebijakan Tata Kelola Dampak Aktivitas Penambang Marmer Berdasarkan Perspektif Sustainable Development - Lina, Astrid Mey (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
The objective of this research study is to provide alternatives related to environmental conservation planning in Tulungagung Regency based on a sustainable development perspective. The results of the analysis show that even though mining management through a number of regulations is able to give an impact on economic growth, it is unable to achieve sustainable development due to lack of attention to socio-economic aspects such as lack of community role and lack of special attention to natural disasters. In general, being able to achieve sustainable development must enhance the role of the community and produce policies that are in accordance with the characteristics of the community and environmental conditions.